2013
DOI: 10.1177/0145445513507574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Good Behavior Game on Classwide Off-Task Behavior in a High School Basic Algebra Resource Classroom

Abstract: This study investigated the effects of the Good Behavior Game (GBG) on classwide off-task behavior in two ninth-grade basic algebra resource classes. Ten students with a variety of disabilities, in two classrooms, and their special education resource teacher participated in this study. A reversal design was employed, in which the special education teacher implemented GBG compared to typical practice-algebra readiness instruction. Results showed that classwide off-task behavior decreased in the GBG conditions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
(62 reference statements)
5
38
0
Order By: Relevance
“…Teachers perceived the effectiveness of GBG in changing student behavior to be aligned with findings from previous research conducted in other countries, emphasizing that GBG is a strategy for classroom intervention that can promote positive changes in students' behavior, as well as provide support for a more effective pedagogical practice (Donaldson, Vollmer, Krous, Downs, & Berard, 2011;Flower et al, 2014;Poduska et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Teachers perceived the effectiveness of GBG in changing student behavior to be aligned with findings from previous research conducted in other countries, emphasizing that GBG is a strategy for classroom intervention that can promote positive changes in students' behavior, as well as provide support for a more effective pedagogical practice (Donaldson, Vollmer, Krous, Downs, & Berard, 2011;Flower et al, 2014;Poduska et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
“…If a member of the team broke a classroom rule, the team would receive a checkmark. Groups received positive feedback and rewards when they did not accumulate more than four checkmarks, following the model proposed in GBG (Flower, McKenna, Muething, Bryant, & Bryant, 2014;Kellam et al, 2014;Tingstrom et al, 2006). Having consequences for rule-breaking and positive reinforcement for following the behavioral expectations created for the classroom increased sociability and better relationships among peers, who started to self-regulate their behaviors.…”
Section: The Brazilian Pilot Interventionmentioning
confidence: 99%
“…Researchers have repeatedly demonstrated the efficacy of the GBG for decreasing disruptive behavior in kindergarten through high school students (e.g., Donaldson, Vollmer, Krous, Downs, & Berard, 2011;Flower, McKenna, Muething, Bryant, & Bryant, 2013;Harris & Sherman, 1973) across a variety of settings, including inclusive classrooms (e.g., Johnson, Turner, & Konarski, 1978) and a cafeteria (McCurdy, Lannie, & Barnabas, 2009). However, several limitations warrant further research.…”
mentioning
confidence: 99%
“…Although the literature is sparse on applications of group contingencies with high school students, the few studies conducted thus far show that they also can be effective in reducing classwide problem behavior with this older population (e.g., Christ & Christ, ; Schanding & Sterling‐Turner, ; Theodore, Bray, & Kehle, ). For example, the Good Behavior Game (GBG; Barrish, Saunders, & Wolf, ), which employs an interdependent group contingency (see Embry, ; Tingstrom, Sterling‐Turner, & Wilczynski, for reviews) and is traditionally used with younger students, has also been found relatively recently to effectively decrease classwide disruptive behavior with high school students (Flower, McKenna, Muething, Bryant, & Bryant, ; Kleinman & Saigh, ; Mitchell, Tingstrom, Dufrene, Ford, & Sterling, ).…”
mentioning
confidence: 99%